1994
DOI: 10.1037/0735-7036.108.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Memory for pictures of upright and inverted primate faces in humans (Homo sapiens), squirrel monkeys (Saimiri sciureus), and pigeons (Columba livia).

Abstract: Humans (Homo sapiens) and squirrel monkeys (Saimiri sciureus) were tested for memory of upright and inverted primate faces. Working memory was tested in Experiment 1 with a delayed matching-to-sample procedure, and reference memory was examined in Experiment 2 by requiring subjects to learn to discriminate between successive pairs of upright or inverted pictures. Both human and monkey subjects showed better working memory for upright than for inverted human faces and better reference memory for upright than fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
3
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 34 publications
3
60
3
1
Order By: Relevance
“…Indeed, the baboons belonging to the control group (trained with upside-down faces) did not depart from the animals of the canonical group in terms of learning speed. This effect seems at odds with previous results showing that humans discriminate upright human and ape faces more easily than upsidedown ones (e.g., Phelps & Roberts, 1994). This latter result is also inconsistent with the observation that a squirrel monkey (Samiri sciureus) showed faster acquisition with upright human and ape faces than with inverted ones (Phelps & Roberts, 1994).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Indeed, the baboons belonging to the control group (trained with upside-down faces) did not depart from the animals of the canonical group in terms of learning speed. This effect seems at odds with previous results showing that humans discriminate upright human and ape faces more easily than upsidedown ones (e.g., Phelps & Roberts, 1994). This latter result is also inconsistent with the observation that a squirrel monkey (Samiri sciureus) showed faster acquisition with upright human and ape faces than with inverted ones (Phelps & Roberts, 1994).…”
Section: Discussioncontrasting
confidence: 57%
“…This effect seems at odds with previous results showing that humans discriminate upright human and ape faces more easily than upsidedown ones (e.g., Phelps & Roberts, 1994). This latter result is also inconsistent with the observation that a squirrel monkey (Samiri sciureus) showed faster acquisition with upright human and ape faces than with inverted ones (Phelps & Roberts, 1994). It should be noted, however, that they only tested 1 monkey in each of their experiments.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Given that most non-human primates have excellent binocular vision and are social animals living in large cohorts, it may be expected that there will exist a system for the visual recognition of conspecifics. Indeed, many studies (Rosenfeld & Van Hoesen 1979;Bruce 1982;Phelps & Roberts 1994;Pascalis et al 1998;Weiss et al 2001) have found evidence for face-recognition abilities in different non-human primate species.…”
Section: Face Identity Recognition and Memory For Faces (A) Face Recomentioning
confidence: 99%
“…They tested the hypothesis with the use of the inversion e ect (whereby humans [e.g. 38,39] monkeys [28,37] and chimpanzees [26] are particularly bad at identifying faces presented upsidedown) and found that dog-show judges demonstrate an equivalent e ect for dogs. Thus they suggest that any visual objects with a common feature con®gur-ation can show face-like e ects if they are discriminated frequently.…”
mentioning
confidence: 99%